Scrutiny of the intricacies of corporate governance and pubilc accountability mechanisms in South African state-owned companies - Shezi, Mthokozisi Gift (Department of Commercial Law, 2026)
State-owned companies play a significant role in the South African economy. At the core of their operations, these state-owned companies provide a variety of services and public utilities, inter alia, transportation, telecommunication, infrastructure, and energy. State-owned companies additionally are formed in the pursuit of state policy objectives and in turn they make provision for public benefit i.e., employment and business opportunities to name a few. Insofar as these companies strive to pursue the aforementioned services and policy objectives, there are deficiencies that exist in respect of their functioning. These deficiencies are, inter alia, lack of good corporate governance practices, harmful interference with state-owned companies (as reported in the State Capture Report), lack of appropriate balance between board autonomy and political interference, financial mismanagement, and more importantly ineffective accountability mechanisms from relevant oversight institutions arguably plague these entities. To this end, there have been numerous notable cases adjudicated concerning state-owned companies' financial reporting irregularities, their policy objectives, and the exercise of powers thereto. In light of the foregoing, this research embarks on a critical analysis of the intricacies between the corporate governance of state-owned companies and public accountability mechanisms in South Africa taking into consideration the Public Finance Management Act 1 of 1999, the Companies Act 71 of 2008, relevant case law, institutional reports, and applicable policy frameworks. The primary objective is to analyse and discuss the effectiveness of governance mechanisms by indicating their strengths and weaknesses. Through this discussion, the research aims to shed light on the challenges encountered by state-owned companies, by critically exploring the intricacies brought by their objectives, policy frameworks, operational challenges, and public accountability obligations. These discussions expose the significant challenges that are faced by state-owned companies and necessitate a need for legislative reform. In conjunction with the primary objective this research further investigates the dynamics and difficulties that are presented from the relations with the Auditor General, Standing Committee on Public Accounts, Department of Public Enterprise, and the portfolio committees as institutions in charge of overseeing state-owned companies from corporate governance and public accountability perspective. This research further exposes concerns surrounding the relationship between the state, and state-owned companies, and the relevancy of portfolio committees in respect of the aforesaid. It submits the existing regime as complex, contradictory and ineffective insofar as accountability is concerned. As a matter of fact, case law and the ground-breaking state capture reports expose the many multifaceted inconsistencies that exist between public accountability mechanisms and the corporate governance of state-owned companies. Insofar as the crucial role that these state-owned companies play in South Africa, it is imperative that these concerns are addressed expeditiously. In essence, this research proposes the review of the current state owned companies' corporate governance framework and the role of public accountability mechanism to propose a singular, effective and practical legal framework that is inclusive of relevant oversight institutions and thus maintains an elevated level of accountability.